Anticancer Activity and Mechanism of Xanthohumol: A Prenylated Flavonoid From Hops (Humulus lupulus L.) - Chuan-Hao Jiang; Tao-Li Sun; Da-Xiong Xiang; Da-Xiong Xiang; Da-Xiong Xiang; Shan-Shan Wei; Shan-Shan Wei; Wen-Qun Li; Wen-Qun Li; Wen-Qun Li (Frontiers Media S.A., 2018)
It has been observed that many phytochemicals, frequently present in foods or beverages, show potent chemopreventive or therapeutic properties that selectively affect cancer cells. Numerous studies have demonstrated the anticancer activity of xanthohumol (Xn), a prenylated flavonoid isolated from hops (Humulus lupulus L.), with a concentration up to 0.96 mg/L in beer. This review aims to summarize the existing studies focusing on the anticancer activity of Xn and its effects on key signaling molecules. Furthermore, the limitations of current studies and challenges for the clinical use of Xn are discussed.